Aggregate consequences of credit subsidy policies: Firm dynamics and misallocation - Hwan Jo; Tatsuro Senga (Queen Mary University of London, School of Economics and Finance, 2017)
Government policies that attempt to alleviate credit constraints faced by small and young firms are widely adopted across countries. We study the aggregate impact of such targeted credit subsidies in a heterogeneous firm model with collateral constraints and endogenous entry and exit. A defining feature of our model is a non-Gaussian process of firm-level productivity, which allows us to capture the skewed firm size distribution seen in the Business Dynamics Statistics (BDS). We compare the welfare and aggregate productivity implications of our non-Gaussian process to those of a standard AR(1) process. While credit subsidies resolve misallocation of resources and enhance aggregate productivity, increased factor prices, in equilibrium, reduce the number of firms in production, which in turn depresses aggregate productivity. We show that the latter indirect general equilibrium effects dominate the former direct productivity gains in a model with the standard AR(1) process, as compared to our non-Gaussian process, under which both welfare and aggregate productivity increase by subsidy policies.
Keywords: E22; G32; O16; 330; misallocation; collateral constraints; firm dynamics; firm size